Domestic violence due to online gambling (Scatter Slots) in Baringin Natam village, Parlilitan district - Loren Buaton; Yusnadi; Muhammad Takwin Machmud (International Journal of Educational Practice and Policy, 2024)
This study aims to analyze Domestic Violence Due to Online Gambling (Scatter Slots) in Baringin Natam village, Parlilitan district. The research method employed is qualitative research with a descriptive approach. Data collection techniques include participatory observation, semi-structured interviews, and documentation. According to research findings, online gambling such Higgs Domino (Scatter Slot) has created disturbing phenomena in the community of Baringin Natam village. Although easily accessible and played flexibly, most participants gather in specific places such as coffee shops. This phenomenon has disrupted the comfort and order of the local community. Factors contributing to the proliferation of online gambling include social networking, ease of access to games, and motivation to earn money. The negative impacts of online gambling, especially Higgs Domino, not only involve economic issues for players but also extend to internal household problems. Online gambling addiction leads to significant financial expenditures, dishonesty in household financial management, and conflicts between spouses. This phenomenon can even result in domestic violence, both verbal and physical. Addressing these issues requires improved prevention and intervention efforts.